2012
DOI: 10.1186/1742-9994-9-28
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic shifts in the Antarctic fish Notothenia rossii in response to rising temperature and PCO2

Abstract: IntroductionOngoing ocean warming and acidification increasingly affect marine ecosystems, in particular around the Antarctic Peninsula. Yet little is known about the capability of Antarctic notothenioid fish to cope with rising temperature in acidifying seawater. While the whole animal level is expected to be more sensitive towards hypercapnia and temperature, the basis of thermal tolerance is set at the cellular level, with a putative key role for mitochondria. This study therefore investigates the physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 82 publications
(118 reference statements)
4
93
1
Order By: Relevance
“…Although temperature increases have long been known to impact oxidative stress in organisms (Lesser, 2006), ocean acidification has recently emerged as a potentially more pressing issue in the world's oceans, and to date, we still have a poor understanding of the cellular-level impact that ecologically relevant increases in seawater Ṗ CO 2 will have on cellular homeostasis. Increases in Ṗ CO2 are specifically hypothesized to exacerbate oxidative stress by directly affecting mitochondrial function (Murphy, 2009;Tomanek et al, 2011), and recent studies have indeed shown that hypercapnia can negatively affect mitochondrial capacities in Antarctic fish (Strobel et al, 2012;Strobel et al, 2013b). We found that oxidative damage was most apparent within the first 7 days of acclimation to the treatment conditions, which coincides with a spike in the resting metabolic rate (RMR) of all three species under these same acclimation conditions (Enzor et al, 2013).…”
Section: Tissue-specific Changes In Antioxidant Capacitymentioning
confidence: 71%
See 3 more Smart Citations
“…Although temperature increases have long been known to impact oxidative stress in organisms (Lesser, 2006), ocean acidification has recently emerged as a potentially more pressing issue in the world's oceans, and to date, we still have a poor understanding of the cellular-level impact that ecologically relevant increases in seawater Ṗ CO 2 will have on cellular homeostasis. Increases in Ṗ CO2 are specifically hypothesized to exacerbate oxidative stress by directly affecting mitochondrial function (Murphy, 2009;Tomanek et al, 2011), and recent studies have indeed shown that hypercapnia can negatively affect mitochondrial capacities in Antarctic fish (Strobel et al, 2012;Strobel et al, 2013b). We found that oxidative damage was most apparent within the first 7 days of acclimation to the treatment conditions, which coincides with a spike in the resting metabolic rate (RMR) of all three species under these same acclimation conditions (Enzor et al, 2013).…”
Section: Tissue-specific Changes In Antioxidant Capacitymentioning
confidence: 71%
“…The initial spike in oxidative damage observed in this study along with the increased metabolic rates previously observed within the first week of acclimation (Robinson and Davison, 2008a;Robinson and Davison, 2008b;Strobel et al, 2012;Enzor et al, 2013) may signal a surge in protein synthesis and turnover as the cellular environment is restructured. The slow decline of metabolic rates seen in previous studies, connected with the precipitous drop-off in damaged proteins seen in this study, may in turn signal that the initial energy expenditure has led to a more stable cellular environment.…”
Section: Predicting Winners and Losers In Global Climate Change Scenamentioning
confidence: 88%
See 2 more Smart Citations
“…Robinson and Davison (Robinson and Davison, 2008) showed that oxygen consumption (Ṁ O 2 ) acclimated to 4°C in P. borchgrevinki after 1 month such that resting Ṁ O 2 was the same as that at −1°C and recovery from exhaustive exercise was the same in warm-or cold-acclimated fish. More recently, metabolic rate stabilisation, mitochondrial function and acid-base regulation have all been used to measure acclimation state in the fish Notothenia rosii, where partial acclimation of metabolic rate was observed after 29-36 days at 7°C (Strobel et al, 2012). At the whole-animal level, Bilyk and DeVries (Bilyk and DeVries, 2011) used the change in CT max to demonstrate that a range of fish from both the high Antarctic at McMurdo Sound and the maritime Antarctic on the Antarctic Peninsula were capable of acclimating to 4°C (Fig.…”
Section: Acclimation In Antarctic Fishmentioning
confidence: 99%